SAT0550 Health-related quality of life in patients with giant cell arteritis treated with tocilizumab in a phase 3 randomised controlled trial. (12th June 2018) - Strand, V.; Dimonaco, S.; Tuckwell, K.; Klearman, M.; Collinson, N.; Stone, J.H.; ,
Abstract : Background: Superior rates of sustained glucocorticoid (GC)–free remission were shown in patients with giant cell arteritis (GCA) treated with weekly or every-other-week (wk) subcutaneous tocilizumab (TCZ) 162 mg +26 wk GC taper for 52 wks compared with placebo +26 wk or 52-wk GC taper (PBO +26 or PBO +52) in the GiACTA trial. Statistically significant improvements in SF-36 Physical Component Summary (PCS) scores were reported for weekly TCZ vs PBO +52 and in patient-reported global assessment of disease activity for both TCZ groups vs both PBO groups. 1 Objectives: To report further analysis of patient-reported outcomes (PROs) in GiACTA. Methods: Analyses of SF-36 PCS and Mental Component Summary (MCS), SF-36 domains, and Functional Assessment of Chronic Illness Therapy (FACIT)–fatigue compared patients treated with weekly TCZ (n=100) vs PBO +26 (n=50; not shown) or PBO +52 (n=51) for 52 wks based on reported data, including all responders as well as patients with post-escape data following flare. Results: Improvements in SF-36 PCS and MCS scores, 6 of 8 SF-36 domains, and FACIT–Fatigue at wk 52 were significantly greater with weekly TCZ vs PBO +52 (p<0.01) (table 1, figure 1). At wk 52, mean scores met or exceeded age/gender (A/G)–matched normative scores in the weekly TCZ group; higher proportions of patients reported scores exceeding A/G norms in SF-36 PCS and MCS, all SF-36 domains, and FACIT-Fatigue (Table) compared with PBO groups. The median cumulative prednisone dose over 52 wks was lower with weekly . TCZ (1862 0 mg) vs PBO +26 (3296.0 mg) or PBO +52 (3817.5 mg) (p<0.01). Conclusions: Patients with GCA treated with weekly TCZ 162 mg and a 26-wk GC taper reported statistically significantly greater improvements in health-related quality of life and fatigue that exceeded normative values compared with those receiving 52-wk GC taper alone, in part ascribed to lower steroid doses. Reference: [1] Stone JH, et al. N Engl J Med2017;377:317–328. Disclosure of Interest: V. Strand Consultant for: AbbVie, Amgen, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Celltrion, CORRONA, Crescendo, EMD Serono, Genentech/Roche, GSK, Janssen, Lily, Merck, Novartis, Pfizer, Protagen, Regeneron, Samsung, Sandoz, Sanofi, UCB, S. Dimonaco Employee of: Roche, K. Tuckwell Shareholder of: Roche, Employee of: Roche, M. Klearman Employee of: Genentech, N. Collinson Employee of: Roche, J. H. Stone Grant/research support from: Roche, Genentech, Xencor, Consultant for: Roche, Genentech, Xencor